Validity and Absolute Reliability of Axial Vertebral Rotation Measurements in Thoracic and Lumbar Vertebrae - José Hurtado-Avilés; Vicente J. León-Muñoz; Pilar Andújar-Ortuño; Fernando Santonja-Renedo; Mónica Collazo-Diéguez; Mercedes Cabañero-Castillo; Ana Belén Ponce-Garrido; Miriam González-Ballester; Francisco Javier Sánchez-Martínez; Pietro G. Fiorita; Nieves Aidé Ruiz-Cambra; Andrés Campuzano-Melgarejo; et al. (Applied Sciences, 2021)
Axial vertebral rotation (AVR) and Cobb angles are the essential parameters to analyse different types of scoliosis, including adolescent idiopathic scoliosis. The literature shows significant discrepancies in the validity and reliability of AVR measurements taken in radiographic examinations, according to the type of vertebra. This study’s scope evaluated the validity and absolute reliability of thoracic and lumbar vertebrae AVR measurements, using a validated software based on Raimondi’s method in digital X-rays that allowed measurement with minor error when compared with other traditional, manual methods. Twelve independent evaluators measured AVR on the 74 most rotated vertebrae in 42 X-rays with the software on three separate occasions, with one-month intervals. We have obtained a gold standard for the AVR of vertebrae. The validity and reliability of the measurements of the thoracic and lumbar vertebrae were studied separately. Measurements that were performed on lumbar vertebrae were shown to be 3.6 times more valid than those performed on thoracic, and with almost an equal reliability (1.38° ± 1.88° compared to −0.38° ± 1.83°). We can conclude that AVR measurements of the thoracic vertebrae show a more significant Mean Bias Error and a very similar reliability than those of the lumbar vertebrae.